Pemanfaatan Abu Tongkol Jagung dan Abu Tempurung Kelapa dalam Pembuatan Pupuk Kalium Silika dengan Metode Sol-Gel - Panggih Syambudi; Anerasari Meidinariasty; Yulianto Wasiran (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
South Sumatra is a province with high agricultural productivity. One of the largest agricultural products is corn and coconut, which is quoted from the website of the Lampung Province Food Security, Food Crops and Horticulture Office in 2021, which states that South Sumatra Province is one of the 10 largest corn producing provinces in Indonesia. With this in mind, the researcher conducted a study using the silica content of corn cobs and coconut husk waste as raw material for the production of potassium silica fertilizer using the sol-gel method. The potassium silicate fertiliser was produced by reacting KOH with corncob ash and coconut husk ash, which were varied. This is because the independent variables used are the concentration of KOH (4M, 6M) and the composition ratio of corn cob ash and coconut shell ash (10:40, 20:30, 25:25, 30:20, 40:10). The final result gave the best sample with more coconut shell ash composition than corn cob ash and higher KOH concentration. The sample formed 12.7 grams of final product with potassium content of 8821 mg/L and water content of less than 1%. As for the silica content in 4:1 coconut shell ash, there is approximately 73.2% silica.